2009
DOI: 10.1021/nl8035367
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based Composite Thin Films for Electronics

Abstract: The electrical properties of solution-processed composite thin films consisting of functionalized graphene sheets (FGS) as the filler and polystyrene (PS) as the host material are described. We demonstrate that transistors from graphene-based composite thin films exhibit ambipolar field effect characteristics, suggesting transport via percolation among FGS in the insulating PS matrix. Device characteristics as a function of the FGS size are also reported. The results indicate that devices fabricated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
387
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(412 citation statements)
references
References 23 publications
11
387
1
3
Order By: Relevance
“…[3][4][5] It is reported that graphene-based polymer nanocomposites show much improved mechanical and electrical properties when compared to other carbon filler based nanocomposites. [6][7][8][9] These unique properties have attracted researchers to investigate graphene as a reinforcing agent in biocompatible composite materials in order to improve mechanical, thermal and electrical properties. [10][11][12][13][14] Poly(ε-caprolactone) (PCl) is a biodegradable and biocompatible aliphatic polyester with good resistance to water, solvents and oil, synthesized by the ring opening polymerization of ε-caprolactone.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] It is reported that graphene-based polymer nanocomposites show much improved mechanical and electrical properties when compared to other carbon filler based nanocomposites. [6][7][8][9] These unique properties have attracted researchers to investigate graphene as a reinforcing agent in biocompatible composite materials in order to improve mechanical, thermal and electrical properties. [10][11][12][13][14] Poly(ε-caprolactone) (PCl) is a biodegradable and biocompatible aliphatic polyester with good resistance to water, solvents and oil, synthesized by the ring opening polymerization of ε-caprolactone.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its special physical and chemical properties, graphene has shown promise for several advanced technological applications, such as graphene-based composites, chemical detectors, fuel cells, and many others [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that graphene is characterised by properties of great potential: breaking strength (≈ 40 N/m), room temperature thermal conductivity (≈ 5000 W m -1 K -1 ), Young modulus (≈ 1 TPa) and so on [4]. Furthermore the electron mobility of graphene (1−2×10 5 cm 2 /Vs) is a hundred times higher than that of silicon [5], so graphene is a material of great potential for use in micro-electronics [6,7]. However the manufacture of integrated circuits needs a transfer printing method on small size of graphene films [8].…”
Section: Introductionmentioning
confidence: 99%